2022
DOI: 10.3389/fmed.2022.941647
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Prevention of Mother-to-Child Transmission of Human T-Cell Lymphotrophic Virus Type 1 (HTLV-1) With a Proposed Management Algorithm

Abstract: Human T cell lymphotropic virus type 1 (HTLV-1) is a human retrovirus that is endemic in a number of regions across the world. There are an estimated 5–10 million people infected worldwide. Japan is currently the only country with a national antenatal screening programme in place. HTLV-1 is primarily transmitted sexually in adulthood, however it can be transmitted from mother-to-child perinatally. This can occur transplacentally, during the birth process or via breastmilk. If HTLV-1 is transmitted perinatally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…The results of HTLV-1 testing of pregnant women in Spain during 2022 showed that prevalence rate has remained stable for two decades. 48,49 However, among Latin American pregnant women was 0.4%, a rate higher than that observed for other infections such as HIV (0.1%−0.26%) 50 or syphilis (0.11%), 51 almost fully stopped avoiding breastfeeding, 53 universal HTLV screening of pregnant women in Spain seems to be justified.…”
Section: Hiv-2 Epidemicsmentioning
confidence: 80%
See 1 more Smart Citation
“…The results of HTLV-1 testing of pregnant women in Spain during 2022 showed that prevalence rate has remained stable for two decades. 48,49 However, among Latin American pregnant women was 0.4%, a rate higher than that observed for other infections such as HIV (0.1%−0.26%) 50 or syphilis (0.11%), 51 almost fully stopped avoiding breastfeeding, 53 universal HTLV screening of pregnant women in Spain seems to be justified.…”
Section: Hiv-2 Epidemicsmentioning
confidence: 80%
“…Finally, around 25% of pregnant women attended in Spain during the last 5 years are foreigners and 80% come from endemic countries for HTLV‐1. Given that vertical transmission is almost fully stopped avoiding breastfeeding, 53 universal HTLV screening of pregnant women in Spain seems to be justified.…”
Section: Interventions Toward the Elimination Of Human Retroviral Epi...mentioning
confidence: 99%
“…To make matters worse, only a few countries screen pregnant women for HTLV antenatally. Finally, if HTLV-1 is transmitted via MTCT, the lifetime risk of developing ATLL rises from 5 to 20% [ 179 ]. Thus, there is a need for further research in HTLV-1 MTCT, which is also highlighted by the recent technical report of the WHO on HTLV-1 [ 180 ].…”
Section: Which Animal Retroviruses From the Family Orthoret...mentioning
confidence: 99%
“…The following interventions were identified in the literature: exclusive formula feeding, shortening the duration of breastfeeding, use of freeze and thaw milk [11][12][13][14][15][16][17], pasteurization of milk [18,19], use of milk bank [13], antiretroviral treatment (maternal and infant) [20][21][22], caesarean section [23], early clamping of umbilical cord [24], screening of milk donors [25,26] and avoidance of wet nursing. Multidisciplinary support for mothers living with HTLV-1 and training of healthcare professionals were also identified as important strategies for the effectiveness of any policy [27].…”
Section: Interventions Available To Prevent Htlv Mtctmentioning
confidence: 99%
“…There is a paucity of data on the risk of HTLV-1 transmission with short-term breastfeeding outside Japan, especially in women considered to have high risk of HTLV-1 transmission, such as those with HTLV-1 associated diseases, those co-infected by Strongyloides, those with high HTLV-1 proviral load and those who already have a child with an HTLV-1 infection [21,60]. Remark 3.…”
Section: Short-term Breastfeedingmentioning
confidence: 99%